LANGUAGE FUNCTION USED BY THE MAIN CHARACTER IN “BLACK PANTHER: WAKANDA FOREVER” MOVIE - Ningrum, Mabella Lola Kris Mulyo; Linuwih, Endar Rachmawaty; Fadilah, Eka (Seminar Nasional Ilmu Terapan, 2023)
This study was mainly aimed to analyze language function found in the main character in Black Panther: Wakanda Forever Movie. The objectives of the study were to find what kind of language function used by the main character in Black Panther: Wakanda Forever movie and its social dimension. This study used descriptive qualitative approach. The writer used theory of language function by Holmes to analyze the kinds of language function and Holmes’s theory to find its social dimension. The data was collected from “Black Panther: Wakanda Forever” movie. The result of this study showed there were eight types of language function used by the main character. They were referential, expressive, directive, heuristic, commissive, phatic, metalinguistic, and poetic function of language. The writer also found there were social distance scale which were intimate, distant, high solidarity, and low solidarity, and two functional scale which were high information content in the main character’s utterances.